Case Report: Severe Hyponatremia in Infants With Urinary Tract Infection - Abu Bakar, Karmila; Jalaludin, Muhammad Y.; Zainal, Nur; Woon, Sze L.; Mohd Zikre, Nurwahida; Samingan, Nurshadia; Ab Rahman, Syaza; Eng, Caroline S. Y. (Frontiers in Pediatrics, 2021)
Introduction: Many reports on investigations and treatments in UTI, however, little have been mentioned with regards to electrolyte abnormalities. Secondary pseudohypoaldosteronism (PHA) in UTI, though less common, is a known association. Features include hyponatremia and concomitant hyperkalemia. Objectives: We aim to highlight this uncommon sequelae in UTI to avoid incorrect diagnosis and unnecessary investigations. Study design: Clinical data of patients admitted and referred to paediatric nephrologist at University Malaya Medical Centre between May 2019 to October 2020 were collated and elaborated. Results and discussion: We report 3 infants with hyponatremia and hyperkalemia during UTI episodes. Two infants were known to have posterior urethral valve (PUV) before the onset of UTI and one infant had UTI which led to investigations confirming the diagnosis of bladder vaginal fistula. The electrolyte derangements were temporary, resolved within 48 to 72 hours of treatment with intravenous fluid and appropriate antibiotic therapy. Out of three, only 1 had a hormonal study which confirms PHA. Reduced aldosterone activity could be due to absolute reduction in aldosterone titer or lack of aldosterone responsiveness at tubular (other tissues) level. In the latter, aldosterone titer is elevated. The infant in our cohort who had hormonal evaluation had the mentioned electrolyte abnormalities with a markedly elevated aldosterone titer. This demonstrated defective action of the hormone at the level of mineralocorticoid receptor. Although the remaining 2 infants had no confirmatory hormonal study, all of them recovered within 48 hours of hospital admission, after receiving appropriate management for the primary problem which was UTI. We observed a slower recovery of hyponatremia in relation to hyperkalemia but none of these infants required salt replacement upon discharge. Conclusion: Infants with severe UTI and deranged electrolytes should be screened for structural abnormality, and vice versa. Not all infants require hormonal screening, but those who required prolonged salt replacement or showed involvement of other systems warrant further evaluation.